Strength and conditioning for skeleton - Mosey, T. (Strength and Conditioning Journal, 2014)
Skeleton is a winter sport where athletes slide a bobsleigh track head first on a sled. The aim of this article was to identify the key performance indicators to optimal skeleton performance. Once these are established, the strength and conditioning professional can introduce training interventions and testing batteries to improve and quantify optimal athletic performance. Methods that target improvements in strength, power, and acceleration should be considered when crafting strength and conditioning programs for skeleton athletes. For a video abstract of this article, see supplemental digital content 1 (see video, http://links.lww.com/scj/a152).